UPAYA KEPAILITAN SEBAGAI ALTERNATIF BURUH MENDAPAT HAKNYA - Soelistyo, Liem Tony Dwi; H A S, Yasin Nur Alamsyah (Mimbar Keadilan, 2021)
The purpose of this research is to find out alternative efforts for workers to get their rights fulfilled through bankruptcy efforts. The research mixes and matches the norms found in the legislation with the facts obtained through interviews with a practitioner in bankruptcy law as a resource person. Legal efforts through bankruptcy can be used as an alternative for workers in demanding their normative rights that are not fulfilled by the company. The requirements for a bankruptcy application that must be fulfilled by workers are that they must have at least 2 (two) creditors, and it must be proven that there are debts that are due and can be collected. However, especially for workers, it is better to go through the PPHI procedure first until a decision is issued so that the lawsuit for bankruptcy is not considered premature by the Panel of Judges of the Commercial Court.Keywords: labor; curator; bankruptcy attemptAbstrakTujuan penelitian untuk mengetahui upaya alternatif buruh untuk mendapat pemenuhan haknya melalui jalur upaya kepailitan. Penelitian memadupadankan antara norma-norma yang ditemukan dalam peraturan perundang-undangan dengan fakta-fakta yang diperoleh melalui wawancara dengan narasumber seorang praktisi dalam hukum kepailitan. Upaya hukum melalui kepailitan dapat dijadikan upaya alternatif bagi buruh dalam menuntut hak-hak normatifnya yang tidak dipenuhi oleh perusahaan. Syarat permohonan kepailitan yang harus dipenuhi oleh buruh adalah setidaknya harus memiliki setidaknya 2 (dua)  kreditur, dan harus dapat dibuktikan terdapat utang yang jatuh waktu dan dapat dilakukan penagihan. Namun khusus bagi buruh lebih baik harus melalui prosedur PPHI terlebih dahulu hingga dikeluarkannya putusan agar gugatan permohonan pailit tidak dianggap prematur oleh Majelis Hakim Pengadilan Niaga.